The Importance Of Ethical and Social Responsibility Perception and Work Experience On Tax Consultant Ethical Decision Making With Machiavellian Personality As A Moderating Variable - Andita Permatasari Radia, Dewi (Journal of Business, Accounting and Finance, 2023)
This study aims to determine the effect of perceptions of the importance of ethics, social responsibility, and work experience on the ethical decision-making of tax consultants with Machiavellian personality as a moderating variable for Tax Consultants registered at the Indonesian Tax Consultants Association (ITCA) Bandung City. The research method uses associative descriptive quantitative and deductive hypotheses with testing using the Statistical Package for the Social Sciences (SPSS). The research sample consisted of 227 tax consultants registered at the ITCA in Bandung City. The results showed that perceptions of the importance of ethics and social responsibility, and work experience influence the ethical decision-making of tax consultants, then the Machiavellian nature as a moderating variable is able to weaken the effect of perceptions of the importance of ethics and social responsibility on ethical decision making of tax consultants and the Machiavellian nature is able to strengthen the effect of work experience on ethical decision making of tax consultants registered at ITCA in Bandung City